2006
DOI: 10.1021/je060247x
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Densities and Derived Thermodynamic Properties of Imidazolium-Based Ionic Liquids

Abstract: This work addresses the experimental measurements of the pressure (0.10 < p/MPa < 10.0) and temperature (293.15 < T/K < 393.15) dependence of the density and derived thermodynamic properties, such as the isothermal compressibility, the isobaric expansivity, the thermal pressure coefficient, and the pressure dependence of the heat capacity of several imidazolium-based ionic liquids (ILs), namely, 1-butyl-3-methylimidazolium tetrafluoroborate, [ . These ILs were chosen to provide an understanding of the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
283
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 390 publications
(328 citation statements)
references
References 29 publications
43
283
2
Order By: Relevance
“…As for the anion influence on the relative interaction strength, a general trend can be established between the cation-anion interaction and the anion molar volumes: the former decreases as the molar volume increases. 16,54 The relevance of these results to the understanding of the measured mutual solubilities is discussed below.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As for the anion influence on the relative interaction strength, a general trend can be established between the cation-anion interaction and the anion molar volumes: the former decreases as the molar volume increases. 16,54 The relevance of these results to the understanding of the measured mutual solubilities is discussed below.…”
Section: Resultsmentioning
confidence: 92%
“…[14][15][16] Water may also act as a cosolvent, for example, increasing the mutual solubilities between alcohols and ILs, or as an antisolvent, reducing the solubility of gases in ILs. [17][18][19][20] The presence of water can also affect the rates and selectivity of reactions involving or carried in ILs.…”
Section: Introductionmentioning
confidence: 99%
“…28 The reagents [C n mim]-[Br] (n ) 2 to 8) and [Li][Tf 2 N] were acquired at IoLiTec with purities of >99% and >98%, respectively. In order to reduce the water content and volatile compounds to negligible values, the ILs individual samples were dried under constant agitation at vacuum (0.1 Pa) and at 353 K, for a minimum of 48 h. After that careful procedure, the ILs purities were checked by 1 H, 13 C, and 19 F NMR spectroscopy being >99% for all ILs. The bromide content was quantified by ion chromatography and was inferior to 100 × 10 -6 in mass fraction for all samples.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9][10] Another factor that makes the knowledge of mutual solubility with water of importance is the way how the presence of water in the ionic liquids can dramatically affect their physical properties such as viscosities, densities, and surface tensions. [11][12][13] Water may also acts as a cosolvent increasing the mutual solubilities between alcohols and ILs 11,14,15 or as an antisolvent reducing the solubility of other compounds, for example, gases and nonpolar compounds, in ionic liquids. 16,17 Furthermore, the presence of water also affects the rates and selectivity of reactions involving or carried out in ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium [67], phosphonium [68] and guanidinium [69] based ILs were also studied. It was observed that the increase of alkyl chain in 1-alkyl-3-methylimidazolium provokes a correspondent decrease on density values as described by Esperança et al [68] and Gardas [70] et al Both independent studies reported a constant augment of the molar volume of the salt per each two -CH 2 -groups (34.4 cm 3 .mol -1 and 33.88 cm 3 .mol -1 , respectively). This progressive augment of molar volume leads to the decrease of density.…”
Section: Relationship Between Structure and Densitymentioning
confidence: 64%